Analyzing and designing energy storage system and charging station from solar energy-lithium ion - Wattimena, Sefnath J.; Laisina, Luwis H.; Pelamonia, Conny O. E. (Indonesian Journal of Multidisciplinary Science, 2023)
This paper presents the design of a battery charging center that will be used optimally by students in the Department of Electrical Engineering, Ambon State Polytechnic (POLNAM, Politeknik Negeri Ambon). This study would like to design a charger station with a load requirement of 145.98 Wh that can be used as a blueprint for future relevant programs. The design of the charger station is based on the results of research that has been conducted in the study. The results of this study have shown that the number of solar panels 100 WP as much as 1 piece, BMS capacity (ICh = 11.6 A and IDch = 31.7 A), SCC capacity 6.125 A 10 A, Inverter 261 Watt 0.5 KW, and battery pack 21.75 Ah.